2019
DOI: 10.1126/scisignal.aat4128
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function guided modeling of chemokine-GPCR specificity for the chemokine XCL1 and its receptor XCR1

Abstract: Chemokines interact with their G protein–coupled receptors (GPCRs) through a two-step, two-site mechanism and, through this interaction, mediate various homeostatic and immune response mechanisms. Upon initial recognition of the chemokine by the receptor, the amino terminus of the chemokine inserts into the orthosteric pocket of the GPCR, causing conformational changes that trigger intracellular signaling. There is considerable structural and functional evidence to suggest that the amino acid composition and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 87 publications
1
13
0
Order By: Relevance
“…Xcr1 is a receptor for chemokines SCYC1 and SCYC2. A previous study suggested that Xcr1 transduced signals by increasing the intracellular calcium ion level [ 45 ]. Therefore, Xcr1 may be an important signal transduction molecule in the osmotic regulation mechanism of the yellow drums.…”
Section: Discussionmentioning
confidence: 99%
“…Xcr1 is a receptor for chemokines SCYC1 and SCYC2. A previous study suggested that Xcr1 transduced signals by increasing the intracellular calcium ion level [ 45 ]. Therefore, Xcr1 may be an important signal transduction molecule in the osmotic regulation mechanism of the yellow drums.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the functional studies published in recent years have shown that the chemokine ligand axis conforms the classical GPCR activation paradigm. 18 , 19 , 20 Once the ligand is stimulated, the G protein dissociates from the corresponding receptor and initiates different signaling events downstream of ligand binding that can eventually lead to various responses, such as cell proliferation, survival, invasion, migration, and gene transcription. 2 , 8 , 17 All chemokines are small, with approximately 20–50% identical sequences between individual chemokines, suggesting homology in their gene sequences and amino acid sequences.…”
Section: Chemokine Systemsmentioning
confidence: 99%
“…The chemokine network is composed of nearly 50 chemokine ligands, 20 GPCRs, and four ACKRs, 17 which play significant roles in the body's immune homeostasis, inflammatory response, viral infection, and tumor progression (Figure 1). Most of the functional studies published in recent years have shown that the chemokine ligand axis conforms the classical GPCR activation paradigm 18–20 . Once the ligand is stimulated, the G protein dissociates from the corresponding receptor and initiates different signaling events downstream of ligand binding that can eventually lead to various responses, such as cell proliferation, survival, invasion, migration, and gene transcription 2,8,17 .…”
Section: Chemokine Systemsmentioning
confidence: 99%
“… 9 XCL1 is thus able to modulate the spatial location and function of both T cells and DCs. Binding of XCL1 to the orthosteric site of XCR1 triggers Ca 2+ efflux from the endoplasmic reticulum (ER), leading to cytoskeleton remodeling and cell migration, 10 followed by XCR1 desensitization and internalization to early endosomes. 11 It is hypothesized that by following a XCL1 chemotactic gradient, XCR1 + cDC1s can migrate toward the site of inflammation, where they take up antigens.…”
Section: Introductionmentioning
confidence: 99%